Modelagem euler-lagrange da evaporação de um spray multicomponente em meio heterogêneo - Martins, Jamille Kessia Araujo (2023)
In the present work, a Discrete Component Model (DCM) based on the analytical solutions of heat transfer and species diffusion equations, together with the Abramzon-Sirignano model, is applied to analyze the heating and evaporation of droplets involving a case of Jet A kerosene spray injection in a highly heated, inert, and heterogeneous environment. The scope of this work is to assess and understand the influence of a heterogeneous inert flow in a spray injection case involving multicomponent evaporation process. One of the main objectives of this work is to develop and comprehend the MFSim code implemented in MFLab, specifically in relation to the multicomponent evaporation routines within the Lagrangian modeling platform. The work is primarily based on the review and analysis of this process in a heterogeneous environment, which resulted in the implementation and incorporation of new routines for computing the mixture diffusivity coefficient and determining the necessary thermodynamic parameters such as density, dynamic viscosity, thermal conductivity, and specific heat. To evaluate this process in an inert gas environment with multiple species, the evaporation of a single droplet in an atmospheric air gas solution was examined. This analysis focused on comparing the evaporative behavior associated with a single-species environment to that of an environment containing multiple species. Finally, a complex injection case involving Jet A kerosene droplets injected into an inert gas environment with multiple species was evaluated. The analysis of this case involved assessing the average mass fractions obtained along domain lines, as well as studying the behavior of associated parameters such as gas temperature and mass and energy source terms. For all evaluated and compared cases, the obtained results demonstrated the expected physical behavior.